Validation of the dynamic load characteristics on a Tidal Stream Turbine when subjected to wave and current interaction. (15th February 2021) - Lloyd, Catherine; Allmark, Matthew; Ordonez-Sanchez, Stephanie; Martinez, Rodrigo; Johnstone, Cameron; Germain, Gregory; Gaurier, Benoit; Mason-Jones, Allan; O'Doherty, Tim
Abstract: A comparison of a tidal turbine's performance and structural loads is conducted using lab-scale numerical models and experimental testing under multiple current-only and wave-current conditions at the IFREMER wave-current flume. Experimental testing, used to validate CFD models, was accomplished using a 0.9 m diameter, 3-bladed tidal turbine and had a blockage ratio of 8% while the turbine was submerged. Initial investigations analysed the performance and loads on the turbine under uniform and profiled current-only conditions. The presence of a profiled velocity gradient was found to have a negligible effect on the average performance characteristics; however, transient thrust, torque and out of plane bending moment loads experienced much greater variations. These load fluctuations were further increased with increasing levels of shear in the velocity profile, while peaks in the turbine loads coincided with its rotational frequency. The addition of regular, Stokes 2 nd Order Theory waves added to the complexity of the flow conditions experienced by the turbine. The effect on the average performance characteristics were negligible while the total turbine thrust and torque fluctuations increased by 35 times that of the current-only cases. Peaks in the loads aligned with the wave surface elevation, indicating the importance of transient analyses of dynamic loads. Highlights: The mode of the streamwise velocity accurately represents predominant flow conditions. Mean turbine performance was unaffected by profiled velocity gradients and waves. The turbine blade loading fluctuations increased with increasing velocity shear. Blade loading fluctuations, due to waves, were the same as the highest shearing velocity. Optimised free surface, multiphase, CFD models were successfully validated experimentally.